Cytokinin profiles in ex vitro acclimatized Eucomis autumnalis plants pre-treated with smoke-derived karrikinolide - Aremu, Adeyemi O; Plačková, Lenka; Novák, Ondřej; Stirk, Wendy A; Doležal, Karel; Van Staden, Johannes (Plant cell reports, 2016)
KEY MESSAGE: The current evidence of regulatory effect of smoke-water (SW) and karrikinolide (KAR(1)) on the concentrations of endogenous cytokinins in plants partly explain the basis for their growth stimulatory activity. Karrikinolide (KAR1) which is derived from smoke-water (SW) is involved in some physiological aspects in the life-cycle of plants. This suggests a potential influence on the endogenous pool (quantity and quality) of phytohormones such as cytokinins (CKs). In the current study, the effect of SW (1:500; 1:1000; 1:1500 v/v dilutions) and KAR1 (10(-7); 10(-8); 10(-9) M) applied during micropropagation of Eucomis autumnalis subspecies autumnalis on the ex vitro growth and CKs after 4 months post-flask duration was evaluated. The interactions of SW and KAR(1) with benzyladenine (BA), α-naphthaleneacetic acid (NAA) or BA+NAA were also assessed. Plants treated with SW (1:500) and KAR1 (10(-8) M) demonstrated superior growth in terms of the rooting, leaf and bulb sizes and fresh biomass than the control and plants treated with BA and BA+NAA. However, plant growth was generally inhibited with either SW (1:500) or KAR1 (10(-8) M) and BA when compared to BA (alone) treatment. Relative to NAA treatment, the presence of KAR(1) (10(-7) M) with NAA significantly increased the leaf area and fresh biomass. Both SW and KAR1-treated plants accumulated more total CKs, mainly isoprenoid-type than the control and NAA-treated plants. The highest CK content was also accumulated in SW (1:500) with BA+NAA treatments. Similar stimulatory effects were observed with increasing concentrations of KAR(1) and BA. The current findings establish that SW and KAR1 exert significant influence on the endogenous CK pools. However, the better growth of plants treated with SW and KAR1 treatments was not exclusively related to the endogenous CKs.
Keywords: Plants, Medicinal; Plant Growth Regulators; výhonky rostlin; Furans; kyseliny naftalenoctové; voda; biomasa; furany; kouř; lipnicovité; Plant Roots; léčivé rostliny; Cytokinins; regulátory růstu rostlin; Naphthaleneacetic Acids; Plant Leaves; Pyrans; Asparagaceae; listy rostlin; Plant Shoots; Water; aklimatizace; cytokininy; Acclimatization; Smoke; pyrany; kořeny rostlin; Biomass; Poaceae